STUDY OF ZZ PRODUCTION AT LEP AT $\sqrt{s} =183 -209\, {\rm GeV} - PÁSZTOR, GABRIELLA (International journal of modern physics. A, Particles and fields, gravitation, cosmology, 2001)
A study of Z boson pair production in e+e- annihilation using the OPAL detector at LEP is reported . The ZZ production cross-section is measured, limits on anomalous ZZγ and ZZZ couplings are derived, and constraints on models of low scale quantum gravity in extra spatial dimensions are set.